Upaya peningkatan kemampuan melakukan senam kebugaran jasmani indonesia bersatu 2018 melalui metode pembiasaan pada siswa kelas vi sekolah dasar - Adliroh, Adliroh (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2020)
The purpose of this study was to determine the success of the application of thehabituation method in improving the ability to suit motion and movement techniques to perform physical fitness exercises (SKJ) in 2018 United Indonesia for 6th grade students of SDNegeri Gedanganak 02, East Ungaran District. Semarang Regency for the 2018/2019 academic year. This research is a Classroom Action Research (PTK). The research subjects are the 6th grade students of SD Negeri Gedanganak 02, East Ungaran Subdistrict, Semarang Regency in the 2018/2019 academic year, totaling 30 students. Data collection techniques used observation and filling weekly tables, while data analysis using descriptive analysis indicatedby the results of the frequency distribution. The results showed that the results of the pre-cycle, most of the students had not yet completed the exercise of the 2018 United Indonesia SKJ gymnastics, a total of 28 students (93.3%), while only 2 students completed (6.7%). Then after the first cycle of assessment-1, students who had completed the 2018 United Indonesia SKJ gymnastics increased to 9 students (30.0%), and on the 2nd assessment students who had completed the 2018 United Indonesia SKJ gymnastics increased to 20 students (66 , 7%).Furthermore, in cycle II, students who had completed the 2018 United Indonesia SKJ gymnastics increased to 26 students (86.7%), so it was concluded that the habituation program as a class action was proven to be effective in improving the ability to practice gymnastics SKJ Indonesia Bersatu 2018 in class students. 6 SD Negeri Gedanganak 02, East Ungaran District. It is recommended for teachers to be able to apply the habituation method in providing learning about the 2018 United SKJ Indonesia Gymnastics to students, because the habituation method has been proven to be effective in improving the 2018 United SKJ Indonesia gymnastics practice for students.